Implementation of Integrated Marketing Communication Yasika 25 - MAHENDRA, Andi Yusuf; MUHAMMAD, Digar Rou Yahya (PT Keberlanjutan Strategis Indonesia, 2023)
Yasika 25 social foundation carries out social marketing communication through social service activities as part of their marketing plan, in an effort to build better relationships with the community, strengthen brand loyalty, increase consumer trust, and expand market reach. This research aims to describe how Yasika 25 social foundation carries out social marketing communication and what tools are used in its implementation. The research method used is qualitative descriptive by conducting interviews with three individuals involved in Yasika 25 marketing activities. The results of the research show that Yasika 25 uses various social marketing tools such as social media, websites, brochures, and social service activities. Social media is the primary tool for social marketing communication to target audiences, such as Instagram and Facebook. The Yasika 25 website is used as an information medium about their social activities and campaigns. In addition, Yasika 25 also uses brochures as a conventional marketing tool to reach communities that are not connected to social media or their website. During social service activities, Yasika 25 uses marketing tools such as banners, flags, and merchandise as branding efforts and to increase community awareness of their social foundation. The results of this research show that Yasika 25 has been successful in carrying out social marketing communication by using effective marketing tools.